The United States–China Trade War: Timeline, Consequences, and Prospects for the US Economy. An Analysis Based on the Textile Industry - Stawasz‑Grabowska, Ewa; Wieloch, Justyna (Comparative Economic Research. Central and Eastern Europe, 2023)
In this paper, we investigate the scale of the drop in American imports after it imposed punitive tariffs on Chinese goods. Our analysis spans the whole period of Donald Trump’s presidency (January 2017 – January 2021). In contrast to existing studies, which are mainly devoted to the impact of reduced trade flows on the key macroeconomic indicators, we focus on the specific market of textile products, which was among the most affected by the protectionism measures. The quantitative analysis allows us to conclude that the imposed duties severely hit the textile industry, bringing a noticeable drop in US imports of selected groups of products from China. Furthermore, the review of long‑term consequences indicates that the ongoing trade war has not only adversely affected the macroeconomic fundamentals of the US economy, but it is also likely to have a long‑lasting impact on global supply and production chains.